Effects of Siraitia grosvenorii seed flour on the properties and quality of steamed bread - Zhou, Wei; Guo, Siyu; Zhang, Sheng; Lu, Zhaodi; Sun, Ziyi; Ma, Yulin; Shi, Jinxiu; Zhang, Hao (Frontiers in Nutrition, 2023)
Siraitia grosvenorii seeds are rich in abundant active compounds beneficial to human health. To clarify the digestion characteristics of Siraitia grosvenorii seed flour (SSF) and promote the use of SSF in the processing of functional staple foods, SSF was prepared, its composition and physicochemical properties were studied, and the processing characteristics of SSF-wheat flour were systematically investigated. The results showed that the torque curve and other parameters of the dough were significantly affected by the amount of SSF added. With the increase of SSF proportion, the water absorption showed an increasing trend, while the degree of protein weakening first weakened and then enhanced. At 20% SSF, the dough was more resistant to kneading. In response to an increase in SSF, the L* value decreased significantly, and the a* and b* values increased gradually, while the specific volume decreased gradually. Additionally, the hardness, adhesiveness, and chewiness of the bread enhanced gradually, while its elasticity, cohesiveness, and resilience decreased gradually. After the addition of 30% SSF, the inner tissue of steamed bread was more delicate. With an increase in SSF proportion, the predicted glycemic index (pGI) of steamed bread weakened markedly. Overall, these results showed that SSF, as a kind of food ingredient with hypoglycemic activity, can be used in the production of new functional steamed bread products. This study provides basic research data for the development of products containing S. grosvenorii seed.